Gating effect of suspended multiwalled carbon nanotube with all-shell rooted from electrodes: parallel growth from ferromagnetic catalytic contact - Lee, YH; Lee, CW; Kim, DH; Jang, YT; Choi, CH; Shin, KS; Ju, BK (ELSEVIER SCIENCE BV, 2004)
We describe the gate coupling of a rooted grown suspended carbon nanotube (CNT) between two microsized catalytic contact electrodes using a direct parallel growth technique. All-shell Multiwalled carbon nanotubes (MWNTs) were bonded to contact electrodes because MWNTs were grown from the electrodes. The response characteristics of the devices with the gate voltage show typical p-type field effect transistor function at a high-temperature regime and asymmetric Coulomb blockage behavior in low temperatures. Results of the observation suggest that our unique structure, i.e., catalytic ferromagnetic electrode/all-shell bonded MWNT/ferromagnetic electrode, made by direct parallel growth may be a promising key element for nanoelectronics and nanoelectro-mechanical-systems (NEMS). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: ELECTRICAL BREAKDOWN; TRANSISTOR